Standing Together or Falling Apart? Understanding Employees’ Responses to Organizational Identity Threats - Piening, Erk P.; Salge, Torsten Oliver; Antons, David; Kreiner, Glen E. (Academy of Management Review, 2020)
How do employees respond to organizational identity threats? Despite its theoretical and practical importance, this question has had surprisingly little research devoted to it. In particular, evidence remains unclear as to whether organizational identity threats lead employees to disidentify with their organization (to protect their individual identities by distancing themselves from the organization) or, in contrast, whether they foster organizational identification and cohesion (to protect the identity of the organization as a whole by rallying around and defending the organization). Based on the integration of social identity theory and attribution theory, we develop a conceptual model that clarifies the process by which employees recognize organizational identity threats as challenging their individual identity, make sense of their underlying causes, and decide how to respond to them.